High-transmission cooling coating and preparation method thereof
By adopting high transmission coating composed of waterproof closed layers, intermediate layers, and surface layers, the problem of poor insulation in the existing technology in the existing technology has been solved, and the high transmission effect is achieved. The window glass cools down.
Patent Information
- Application Number
- CN202411667712.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The thermal insulation effect of existing cooling coatings is difficult to meet the society's demand for energy conservation, environmental protection and comfort, especially in high temperature environments.
A high-transmission cooling coating composed of a waterproof sealing layer, an intermediate layer and a surface layer is used. The waterproof sealing layer is composed of low molecular weight epoxy resin, reactive diluent and wetting agent, and the middle layer is composed of polyurethane resin, functional materials and dispersants. Composed, the surface layer is composed of hybrid resin, additives and solvents.
It realizes high transmission, good durability and cooling effect, can maintain stable performance in high temperature environments, and is suitable for windows of windows to cool down.
Smart Images

Figure CN119350948A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation, and particularly relates to a high-transmittance cooling coating and a preparation method thereof. Background Art
[0002] With the development of modern industry, the global temperature is also warming, and the summer temperature has repeatedly hit new highs. Cars have also become a means of transportation that modern people cannot do without. However, in the high temperature of summer, if the car is not cooled by air conditioning or other means, solar radiation can enter the car through the glass under static conditions, causing the temperature inside the car to rise to 50 or 60 degrees Celsius, affecting people's use experience. In addition, ultraviolet rays can also cause damage to the skin of passengers, and in severe cases, it can cause diseases such as skin cancer.
[0003] Therefore, cooling the car windows has become an inevitable choice. If cooling cloth is used, it needs to be flipped before and after use, which is a cumbersome process. Therefore, it is a good choice to prepare a cooling coating on the glass. The cooling coating prepared by the existing technology has a heat insulation effect that cannot meet people's needs. As society pays more attention to energy saving, environmental protection, and comfort requirements, new requirements have been put forward for heat insulation and cooling films. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a high-transmittance cooling coating and a preparation method thereof to solve the above-mentioned problems.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a high-transmittance cooling coating, which consists of a waterproof sealing layer, an intermediate layer, and a surface layer;
[0007] The waterproof sealing layer is composed of a low molecular weight epoxy resin, a reactive diluent, and a wetting agent; the low molecular weight epoxy resin is a mixture of Epon-828 and YD-128; the reactive diluent is composed of two or more of allyl glycidyl ether, acrylate, and vinyl ether; the wetting agent is composed of silicone, polyether, polyester, fatty alcohol, surfactant, and ethanol;
[0008] The intermediate layer is composed of polyurethane resin, functional materials and dispersants; the functional materials include ultrafine phase change powder, aerogel powder and hollow microspheres; the ultrafine phase change powder is ferric oxide, the aerogel powder is silicon dioxide aerogel, and the hollow microspheres are hollow ceramic microspheres; the dispersant is zinc stearate;
[0009] The surface layer is composed of hybrid resin, auxiliary material and a first solvent; the hybrid resin is an organic resin and an inorganic resin, the organic resin is an acrylic resin, the inorganic resin is a nano-ceramic resin, the auxiliary material is composed of titanium dioxide, reflective black pigment and ceramic far-infrared radiation powder; the solvent is deionized water.
[0010] Furthermore, the surfactant is composed of sodium octadecyl sulfate and sodium stearate, and the particle size of the ultrafine phase change powder is between 120-180 μm.
[0011] Furthermore, the reflective black pigment is iron chrome black pigment or BASF L0082 perylene black pigment.
[0012] Furthermore, a method for preparing a high-transmittance cooling coating is also provided, which is characterized by comprising the following steps:
[0013] S1. Mix low molecular weight epoxy resin, active diluent and wetting agent, and stir evenly to form a waterproof sealing layer;
[0014] S2, after mixing the ultrafine phase change powder and the polyurethane resin, add the aerogel powder, the dispersant and the hollow microspheres and stir evenly;
[0015] S3, add the hybrid resin to the solvent and mix evenly, then add 1 / 2 of the auxiliary material and mix evenly; after stirring and grinding, add the remaining 1 / 2 of the auxiliary material and continue mixing;
[0016] S4. After cleaning, polishing and removing impurities from the surface of the substrate, apply a waterproof sealing layer, let it stand for 5-10 minutes, and then apply an intermediate layer when it is not completely dry. Let it stand for another 5-10 minutes, and then apply a surface layer when it is not completely dry. Then dry to obtain a high-transmittance cooling coating.
[0017] The steps S1, S2 and S3 can be performed simultaneously.
[0018] Furthermore, in step S1, the mass ratio of low molecular weight epoxy resin, active diluent and wetting agent is 6-8.5:1.5-2.3:1-1.5; the stirring speed is 300-500 rpm / min, and the dispersion time is 12-18 min.
[0019] Furthermore, in the step S2, the mass ratio of the polyurethane resin, the functional material and the dispersant is 2-4:5-7:1-1.5; and in the functional material, the mass ratio of the ultrafine phase change powder, the aerogel powder and the hollow microspheres is 3-4.5:0.5-1:1.5.
[0020] Furthermore, in step S2, the stirring rate of the ultrafine phase change powder and the polyurethane resin is 400-600 rpm / min, the stirring time is 20-25 min, and the stirring time of adding the aerogel powder, the dispersant and the hollow microspheres is 15-25 min.
[0021] Furthermore, in step S3, the mass ratio of the hybrid resin, the auxiliary material and the solvent is 4-7:1-2.7:0.5-1; the mass ratio of the titanium dioxide, the reflective black pigment and the ceramic far-infrared radiation powder in the auxiliary material is 0.5-1.5:0.2-0.5:0.3-0.7.
[0022] Furthermore, in step S3, the hybrid resin is added to the solvent and the mixing stirring rate is 300-500 rpm / min, the stirring time is 20-25 min, and the stirring time after adding the auxiliary material is 15-25 min.
[0023] Furthermore, the high-transmittance cooling coating is used for cooling vehicle window glass.
[0024] The beneficial effects of the present invention are:
[0025] 1. In the present invention, the waterproof sealing layer ensures the stability and durability of the coating as a whole, wherein the low molecular weight epoxy resin has excellent adhesion and chemical corrosion resistance, and the selected Epon 828 and YD-128 have excellent chemical stability and heat resistance, and the primer prepared after mixing with the active diluent and wetting agent can be firmly attached to the surface of the substrate. For example, ethanol has a strong viscosity, and adding it to the waterproof sealing layer can increase its viscosity, making it easier to apply and fix on the surface of the substrate, and reducing the bubbling and peeling phenomenon on the coating surface.
[0026] 2. In the present invention, the middle layer is used for wear resistance and reducing coating wear. The polyurethane resin has excellent elasticity and wear resistance. Placing it in the middle can reduce the damage of the coating. The polyurethane resin has good weather resistance and chemical corrosion resistance and can maintain stable performance in a high temperature environment. The ultrafine phase change powder in the middle layer undergoes phase change in different temperature ranges and absorbs heat. The polyurethane resin is used as a substrate, and ferric oxide is used as a filler to interact with each other through physical effects. It has good permeability to visible light and absorbs ultraviolet light. The ceramic microbeads are evenly dispersed in the polyurethane resin to fill the polyurethane resin. The introduction of silica aerogel can significantly improve the hardness, wear resistance, weather resistance and chemical corrosion resistance of the coating, and has excellent thermal insulation performance. The addition of zinc stearate can increase the antibacterial and lubricity of the middle layer and improve the use value of the middle layer.
[0027] 3. In the present invention, the surface layer is used for cooling and heat insulation, wherein acrylic resin has good weather resistance and UV resistance, high gloss and durability, and can keep the surface smooth in a high temperature environment; nano-ceramic resin is processed by nanotechnology, has excellent adhesion and super wear resistance, can effectively isolate heat transfer, significantly reduce the temperature of the surface of the object, thereby achieving a cooling effect, and can maintain stable performance in a high temperature environment, with excellent temperature resistance, and since it does not contain harmful additives, no harmful gases are generated at room temperature or high temperature; titanium dioxide and reflective black pigment can reflect visible light and near-infrared light in sunlight to reduce heat absorption; ceramic far-infrared radiation powder can radiate heat to the atmosphere within a specific wavelength range to achieve passive cooling; the first solvent is used to adjust the viscosity and performance of the coating.
[0028] 4. The high-transmittance cooling coating and preparation method of the present invention have simple raw materials, convenient preparation, significant innovation and practicality, and can meet the current society's urgent needs for high efficiency, environmental protection, and energy saving.
[0029] 5. The present invention prepares high-transmittance cooling coatings, and each coating is not completely dry during coating, which can make the molecules of the coating move and make the coating connection more firmly.
[0030] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art may be taught from the practice of the present invention. The objectives and other advantages of the present invention may be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to make the purpose, technical solution and beneficial effects of the invention clearer, the present invention provides the following drawings for illustration:
[0032] Figure 1 The present invention is a flow chart for preparing the cooling film. DETAILED DESCRIPTION
[0033] Example 1
[0034] S1. Mix low molecular weight epoxy resin (a mixture of Epon-828 and YD-128), active diluent (consisting of allyl glycidyl ether, acrylate, and vinyl ether), and wetting agent (organic silicon, polyether, polyester, fatty alcohol, sodium octadecyl sulfate, sodium stearate, and ethanol) in a mass ratio of 7:2.3:1, and disperse at 300 rpm / min for 12 minutes to form a waterproof sealing layer;
[0035] S2, preparing polyurethane resin, functional material, and zinc stearate in a mass ratio of 2:6:1.5, wherein the mass ratio of ferric oxide, silica aerogel, and hollow ceramic microspheres in the functional material is 4:0.75:1.5; firstly mixing ferric oxide with polyurethane resin at 400 rpm / min, stirring for 20 min, then adding silica aerogel, zinc stearate, and hollow ceramic microspheres, and continuing to stir at the same rate for 15 min;
[0036] S3, prepare hybrid resin, auxiliary material, and solvent in a mass ratio of 6:2.5:0.5, wherein the mass ratio of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder in the auxiliary material is 0.9:0.5:0.7; add acrylic resin and nano-ceramic resin to deionized water and mix evenly, then add 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and mix evenly; after stirring and grinding, add the remaining 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and continue mixing;
[0037] S4. After cleaning, polishing and removing impurities from the surface of the substrate, apply a waterproof sealing layer, let it stand for 5 minutes, and then apply the middle layer when it is not completely dry. Let it stand for another 5 minutes, and then apply the surface layer when it is not completely dry. After drying, a high-transmittance cooling coating can be obtained.
[0038] Example 2
[0039] S1. Mix low molecular weight epoxy resin (a mixture of Epon-828 and YD-128), active diluent (consisting of allyl glycidyl ether, acrylate, and vinyl ether), and wetting agent (organic silicon, polyether, polyester, fatty alcohol, sodium octadecyl sulfate, sodium stearate, and ethanol) in a mass ratio of 8.5:2..3:1.5, and disperse at 300 rpm / min for 12 minutes to form a waterproof sealing layer;
[0040] S2, prepare polyurethane resin, functional material, zinc stearate in a mass ratio of 4:7:1.5, wherein the mass ratio of ferric oxide, silica aerogel, and hollow ceramic microspheres in the functional material is 4.5:1:1.5; firstly mix ferric oxide with polyurethane resin at 400 rpm / min, stir for 20 min, then add silica aerogel, zinc stearate, and hollow ceramic microspheres, and continue to stir at the same rate for 15 min;
[0041] S3, prepare hybrid resin, auxiliary material, and solvent in a mass ratio of 4:2.7:1, wherein the mass ratio of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder in the auxiliary material is 1.5:0.5:0.7; add acrylic resin and nano-ceramic resin to deionized water and mix evenly, then add 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and mix evenly; after stirring and grinding, add the remaining 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and continue mixing;
[0042] S4. After cleaning, polishing and removing impurities from the surface of the substrate, apply a waterproof sealing layer, let it stand for 5 minutes, and then apply the middle layer when it is not completely dry. Let it stand for another 5 minutes, and then apply the surface layer when it is not completely dry. After drying, a high-transmittance cooling coating can be obtained.
[0043] The difference between Example 2 and Example 1 is that the mass ratio of each raw material is different.
[0044] Example 3
[0045] S1. Mix low molecular weight epoxy resin (a mixture of Epon-828 and YD-128), active diluent (consisting of allyl glycidyl ether, acrylate, and vinyl ether), and wetting agent (organic silicon, polyether, polyester, fatty alcohol, sodium octadecyl sulfate, sodium stearate, and ethanol) in a mass ratio of 7:2.3:1, and disperse at 300 rpm / min for 12 minutes to form a waterproof sealing layer;
[0046] S2, preparing polyurethane resin, functional material, and zinc stearate in a mass ratio of 2:6:1.5, wherein the mass ratio of ferric oxide, silica aerogel, and hollow ceramic microspheres in the functional material is 4:0.75:1.5; firstly mixing ferric oxide with polyurethane resin at 400 rpm / min, stirring for 20 min, then adding silica aerogel, zinc stearate, and hollow ceramic microspheres, and continuing to stir at the same rate for 15 min;
[0047] S3, prepare hybrid resin, auxiliary material, and solvent in a mass ratio of 6:2.5:0.5, wherein the mass ratio of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder in the auxiliary material is 0.9:0.5:0.7; add acrylic resin and nano-ceramic resin to deionized water and mix evenly, then add 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and mix evenly; after stirring and grinding, add the remaining 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and continue mixing;
[0048] S4. After cleaning, polishing and removing impurities from the surface of the substrate, apply a waterproof sealing layer, let it stand for 5 minutes, and then apply the middle layer when it is not completely dry. Let it stand for another 5 minutes, and then apply the surface layer when it is not completely dry. After drying, a high-transmittance cooling coating can be obtained.
[0049] The difference between Example 3 and Example 1 is that the mass ratio of each raw material is different.
[0050] In order to demonstrate the superiority of the raw materials, proportions and preparation methods of the present invention, based on Example 1, Comparative Examples 1 to 4 are set up herein.
[0051] S1. Mix low molecular weight epoxy resin (a mixture of Epon-828 and YD-128), active diluent (consisting of allyl glycidyl ether, acrylate, and vinyl ether), and wetting agent (organic silicon, polyether, polyester, fatty alcohol, sodium octadecyl sulfate, sodium stearate, and ethanol) in a mass ratio of 10:1:1, and disperse at 300 rpm / min for 12 minutes to form a waterproof sealing layer;
[0052] S2, preparing polyurethane resin, functional material, and zinc stearate in a mass ratio of 5:3:3, wherein the mass ratio of ferric oxide, silica aerogel, and hollow ceramic microspheres in the functional material is 1:1:1; firstly mixing ferric oxide with polyurethane resin at 400 rpm / min, stirring for 20 min, then adding silica aerogel, zinc stearate, and hollow ceramic microspheres, and continuing to stir at the same rate for 15 min;
[0053] S3, prepare hybrid resin, auxiliary material, and solvent in a mass ratio of 3:3:3, wherein the mass ratio of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder in the auxiliary material is 1:1:1; add acrylic resin and nano-ceramic resin to deionized water and mix evenly, then add 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and mix evenly; after stirring and grinding, add the remaining 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and continue mixing;
[0054] S4. After cleaning, polishing and removing impurities from the surface of the substrate, apply a waterproof sealing layer, let it stand for 5 minutes, and then apply the middle layer when it is not completely dry. Let it stand for another 5 minutes, and then apply the top layer when it is not completely dry. Then dry to obtain the coating.
[0055] The difference between Comparative Example 1 and Example 1 is that the mass ratio of each raw material is not within the scope of the present invention, and the obtained coating has low transmittance and is too sticky, and cannot be effectively applied to industrial applications.
[0056] Comparative Example 2
[0057] S1. Disperse low molecular weight epoxy resin (mixture of Epon-828 and YD-128) and active diluent (consisting of allyl glycidyl ether, acrylate, and vinyl ether) at a mass ratio of 7:2.3 at 300 rpm / min for 12 min to form a waterproof sealing layer;
[0058] S2. Prepare polyurethane resin and zinc stearate in a mass ratio of 2:1.5; mix the polyurethane resin and zinc stearate, and stir at 400 rpm / min for 20 minutes;
[0059] S3, preparing hybrid resin and solvent in a mass ratio of 6:0.5; adding acrylic resin and nano-ceramic resin into deionized water and mixing evenly;
[0060] S4. After cleaning, polishing and removing impurities from the surface of the substrate, apply a waterproof sealing layer, let it stand for 5 minutes, and then apply the middle layer when it is not completely dry. Let it stand for another 5 minutes, and then apply the top layer when it is not completely dry. Then dry to obtain the coating.
[0061] The difference between Comparative Example 2 and Example 1 is that no wetting agent is added to the waterproof sealing layer, no functional material is added to the middle layer; no auxiliary material is added to the surface layer, and the prepared coating is prone to peeling and edge lifting, and small bubbles exist after coating, and cannot be effectively adapted to industrial applications.
[0062] Comparative Example 3
[0063] S1. Mix polypropylene resin, active diluent (consisting of allyl glycidyl ether, acrylate, vinyl ether), and wetting agent (organic silicon, polyether, polyester, fatty alcohol, sodium octadecyl sulfate, sodium stearate, ethanol) in a mass ratio of 7:2.3:1, and disperse at 300 rpm / min for 12 minutes to form a waterproof sealing layer;
[0064] S2, prepare polypropylene resin, functional material, zinc stearate in a mass ratio of 2:6:1.5, wherein the mass ratio of ferric oxide, silica aerogel, and hollow ceramic microspheres in the functional material is 4:0.75:1.5; firstly mix ferric oxide with polyurethane resin at 400 rpm / min, stir for 20 min, then add silica aerogel, zinc stearate, and hollow ceramic microspheres, and continue to stir at the same rate for 15 min;
[0065] S3, prepare polypropylene resin, auxiliary material, and solvent in a mass ratio of 6:2.5:0.5, wherein the mass ratio of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder in the auxiliary material is 0.9:0.5:0.7; add polypropylene resin to deionized water and mix evenly, then add 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and mix evenly; after stirring and grinding, add the remaining 1 / 2 of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder and continue mixing;
[0066] S4. After cleaning, polishing and removing impurities from the surface of the substrate, apply a waterproof sealing layer, let it stand for 5 minutes, and then apply the middle layer when it is not completely dry. Let it stand for another 5 minutes, and then apply the top layer when it is not completely dry. Then dry to obtain the coating.
[0067] The difference between Comparative Example 3 and Example 1 is that the low molecular weight epoxy resin, polyurethane resin and hybrid resin in the waterproof sealing layer are replaced by polypropylene resin, and the obtained coating cannot be effectively adhered, has poor chemical resistance, and cannot be effectively adapted to industrial applications.
[0068] Comparative Example 4
[0069] S1. Low molecular weight epoxy resin (mixture of Epon-828 and YD-128), active diluent (consisting of propylene glycidyl ether, acrylate, vinyl ether), wetting agent (organic silicon, polyether, polyester, fatty alcohol, sodium octadecyl sulfate, sodium stearate, ethanol), polyurethane resin, functional material, zinc stearate, hybrid resin, auxiliary material, solvent are mixed in a mass ratio of 7:2.3:1:2:6:1.5:6:2.5:0.5, and stirred at 400rpm / min for 20min, and then coated on the surface of the substrate. (The mass ratio of ferric oxide, silica aerogel, and hollow ceramic microspheres in the functional material is 4:0.75:1.5; the mass ratio of titanium dioxide, reflective black pigment, and ceramic far-infrared radiation powder in the auxiliary material is 0.9:0.5:0.7).
[0070] The difference between Comparative Example 4 and Example 1 is that the coating is not prepared according to the method of the present invention, but all the raw materials are directly mixed, and the obtained coating cannot be effectively adapted to industrial applications.
[0071] The substrates coated with the high-transmittance cooling coatings of Examples 1 to 3, the coatings of Comparative Examples 1 to 4, and the substrates without coatings were placed in the same environment to simulate natural conditions such as high temperature, rain, wind and snow to test the performance of the products in the natural environment. The results are shown in Table 1:
[0072] Table 1
[0073]
[0074]
[0075] According to the test results in Table 1, it can be seen that the coatings prepared by Examples 1 to 3 using the raw materials, methods, and ratios of the present invention have high transmittance, moderate bonding strength, and the coating products have appropriate consistency, can effectively reduce temperature, and are suitable for vehicle window applications. However, Comparative Examples 1 to 4, which are not prepared using the present invention, have average transmittance properties of the coatings due to changes in methods, ratios, and raw materials. They are either too sticky, or have insufficient viscosity, or have inappropriate consistency, and have poor cooling properties, and cannot be effectively used for vehicle window applications. In summary, only coatings prepared using the methods, raw materials, and ratios of the present invention can be adapted to vehicle window applications, and changing the conditions will affect the performance of the product.
[0076] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A high-transmittance cooling coating, characterized in that: The cooling coating is composed of a waterproof sealing layer, an intermediate layer and a surface layer; The waterproof sealing layer is composed of a low molecular weight epoxy resin, a reactive diluent, and a wetting agent; the low molecular weight epoxy resin is a mixture of Epon-828 and YD-128; the reactive diluent is composed of two or more of allyl glycidyl ether, acrylate, and vinyl ether; the wetting agent is composed of silicone, polyether, polyester, fatty alcohol, surfactant, and ethanol; The intermediate layer is composed of polyurethane resin, functional materials and dispersants; the functional materials include ultrafine phase change powder, aerogel powder and hollow microspheres; the ultrafine phase change powder is ferric oxide, the aerogel powder is silicon dioxide aerogel, and the hollow microspheres are hollow ceramic microspheres; the dispersant is zinc stearate; The surface layer is composed of hybrid resin, auxiliary materials and solvent; the hybrid resin is organic resin and inorganic resin, the organic resin is acrylic resin, the inorganic resin is nano-ceramic resin, the auxiliary materials are composed of titanium dioxide, reflective black pigment and ceramic far-infrared radiation powder; the solvent is deionized water.
2. The high transmittance cooling coating according to claim 1, characterized in that: The surfactant is composed of sodium octadecyl sulfate and sodium stearate, and the particle size of the ultrafine phase change powder is between 120 and 180 μm.
3. The high transmittance cooling coating according to claim 1, characterized in that: The reflective black pigment is iron chrome black pigment or BASF L0082 perylene black pigment.
4. The high-transmittance cooling coating according to any one of claims 1 to 3, further comprising a method for preparing the high-transmittance cooling coating, characterized in that: The following steps are included: S1. Mix low molecular weight epoxy resin, active diluent and wetting agent, and stir evenly to form a waterproof sealing layer; S2, after mixing the ultrafine phase change powder and the polyurethane resin, add the aerogel powder, the dispersant and the hollow microspheres and stir evenly; S3, add the hybrid resin to the solvent and mix evenly, then add 1 / 2 of the auxiliary material and mix evenly; after stirring and grinding, add the remaining 1 / 2 of the auxiliary material and continue mixing; S4. After cleaning, polishing and removing impurities from the surface of the substrate, apply a waterproof sealing layer, let it stand for 5-10 minutes, and then apply an intermediate layer when it is not completely dry. Let it stand for another 5-10 minutes, and then apply a surface layer when it is not completely dry. Then dry to obtain a high-transmittance cooling coating. The steps S1, S2 and S3 can be performed simultaneously.
5. The method for preparing a high-transmittance cooling coating according to claim 4, characterized in that: In the step S1, the mass ratio of the low molecular weight epoxy resin, the active diluent and the wetting agent is 6-8.5:1.5-2.3:1-1.5; the stirring speed is 300-500 rpm / min, and the dispersion time is 12-18 min.
6. The method for preparing a high-transmittance cooling coating according to claim 4, characterized in that: In the step S2, the mass ratio of polyurethane resin, functional material and dispersant is 2-4:5-7:1-1.5; in the functional material, the mass ratio of ultrafine phase change powder, aerogel powder and hollow microspheres is 3-4.5:0.5-1:1.
5.
7. The method for preparing a high-transmittance cooling coating according to claim 6, characterized in that: In the step S2, the stirring rate of the ultrafine phase change powder and the polyurethane resin is 400-600 rpm / min, the stirring time is 20-25 min, and the stirring time of adding the aerogel powder, the dispersant and the hollow microspheres is 15-25 min.
8. The method for preparing a high-transmittance cooling coating according to claim 4, characterized in that: In the step S3, the mass ratio of the hybrid resin, the auxiliary material and the solvent is 4-7: 1-2.7: 0.5-1; the mass ratio of the titanium dioxide, the reflective black pigment and the ceramic far-infrared radiation powder in the auxiliary material is 0.5-1.5: 0.2-0.5: 0.3-0.
7.
9. The method for preparing a high-transmittance cooling coating according to claim 8, characterized in that: In the step S3, the hybrid resin is added to the solvent and the mixing and stirring rate is 300-500 rpm / min, the stirring time is 20-25 min, and the stirring time after adding the auxiliary material is 15-25 min.
10. The high transmittance cooling coating according to any one of claims 1 to 3, used for cooling vehicle window glass.